2018
DOI: 10.4236/ojl.2018.73012
|View full text |Cite
|
Sign up to set email alerts
|

Schooling for Digital Citizens

Abstract: This study explored the Lebanese teachers' perceptions regarding their knowledge, practice and self-efficacy pertaining to digital citizenship. Data were collected from 378 teacher participants from public schools in Beirut, Lebanon. The study used mixed methods employing an adapted form of Rible's (2015) survey on digital citizenship, alongside a structured focus group interview with 8 teachers drawn randomly from the pool of participant schools. Findings suggest that Lebanese teachers have dispersed and unba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
5
0
3
Order By: Relevance
“…El 43.6% de los estudios presentaron un diseño cuantitativo debido al interés por medir los niveles de conocimiento de todas o algunas dimensiones del constructo (Ghamrawi, 2018) por medio de instrumentos especializados diseñados para ese propósito (Tabla 5). Los estudios cualitativos abarcan el 30.8% de la muestra, cuyo interés fue analizar la percepción que los sujetos tiene del fenómeno (Cubukcu & Bazyan, 2016).…”
Section: Diseños De Investigación E Instrumentos De Recolección De Datosunclassified
See 1 more Smart Citation
“…El 43.6% de los estudios presentaron un diseño cuantitativo debido al interés por medir los niveles de conocimiento de todas o algunas dimensiones del constructo (Ghamrawi, 2018) por medio de instrumentos especializados diseñados para ese propósito (Tabla 5). Los estudios cualitativos abarcan el 30.8% de la muestra, cuyo interés fue analizar la percepción que los sujetos tiene del fenómeno (Cubukcu & Bazyan, 2016).…”
Section: Diseños De Investigación E Instrumentos De Recolección De Datosunclassified
“…Un grupo de investigaciones se enfocaron exclusivamente en la percepción que los docentes construyen del fenómeno (Ata y Yildirim, 2019;Baydar, 2022;Cubukcu y Bazyan, 2016;Dedebali y Dasdemir, 2019;Gazi, 2016;Ghamrawi, 2018;Hui y Campbell, 2018;Kansu y Öksüz, 2019;Karaatmaca et al, 2020;Karaduman, 2017;Martin et al, 2019;Martin et al, 2020;Peart et al, 2020;Soykan y Keser, 2018;Torres et al, 2019;Triastuti, 2019). Estas investigaciones no abordan la construcción del significado pedagógico de ciudadanía digital (Tabla 7).…”
Section: Artículos Agrupados Por Metacategoríasunclassified
“…The stage of feedback and behaviour analysis: (Analysis and Feedback) is the stage of providing opportunities for individuals to discuss their uses of digital technologies, leading to the stage of freedom to provide constructive criticism, and recognition of the proper use of technology (Ben Ltaifa and Derbali, 2022). Digital citizenship has three axes that have been agreed upon by many studies (Aðalsteinsson et al, 2014;Almomani et al, 2021;Ghamrawi, 2018). These axes have been identified in order to help contribute to preparing the modern citizen who is able to use digital technology and its proper and safe use.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The definition of "Digital Natives" identifies individuals who have adjusted to the opportunity to use digital technologies in human life and through intellectual processes (Bittman, Rutherford, Brown, & Unsworth, 2011). Most researchers see that technology plays a significant role for students in this modern era and finds them representing digital natives, as they spend more time in digital relationships than in family or school environments (Ghamrawi, 2018). Studies have shown that internet usage affected adolescents' psychological, emotional, and physical growth as they tend to be under control (Orth & Chen, 2013).…”
Section: Digital Citizenshipmentioning
confidence: 99%